2022
DOI: 10.1186/s12905-022-01934-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine and menstrual conditions in female: data analysis of the Vaccine Adverse Event Reporting System (VAERS)

Abstract: Background In reports of adverse reactions following vaccination with the coronavirus disease 2019(COVID-19) vaccines, there have been fewer reports of concern for menstrual disorders in female. Objective Our study employed Vaccine Adverse Event Reporting System (VAERS) to investigate and analyze the relationship between COVID-19 Vaccines and menstrual disorders in female. Methods We collected reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
0
24
2
1
Order By: Relevance
“…The specific mechanisms through which COVID-19 vaccines may trigger autoimmune reactions are unknown. The COVID-19 vaccine has been related to an increase in the occurrence of blistering illnesses such as bullous pemphigoid [ 22 ]. After COVID-19 immunization, there was a significant clonality of T cells reacting to SARS-CoV-2-associated epitopes in lesions from patients with new-onset bullous pemphigoid, which was not the case before COVID-19 mass immunizations.…”
Section: Covid-19 Vaccines and Premature Autoimmune Spectrum Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific mechanisms through which COVID-19 vaccines may trigger autoimmune reactions are unknown. The COVID-19 vaccine has been related to an increase in the occurrence of blistering illnesses such as bullous pemphigoid [ 22 ]. After COVID-19 immunization, there was a significant clonality of T cells reacting to SARS-CoV-2-associated epitopes in lesions from patients with new-onset bullous pemphigoid, which was not the case before COVID-19 mass immunizations.…”
Section: Covid-19 Vaccines and Premature Autoimmune Spectrum Disordersmentioning
confidence: 99%
“…The majority of NCDs associated with COVID-19 vaccines account for: (1) CVDs including hypertension, myocarditis, infarctions, thromboembolic events, and arrhythmia [ 3 , 8 , 9 , 10 ]; (2) premature obesity and diabetes [ 11 , 12 , 13 , 14 , 15 ]; (3) acute kidney disorders (AKDs) [ 16 ]; and (4) premature neurodegeneration and mental disorders [ 17 , 18 , 19 , 20 , 21 ], and autoimmune spectrum disorders including vaccine-induced immune thrombotic thrombocytopenia (VITT) and leukocytoclastic vasculitis [ 22 , 23 ]. Other systemic adverse reactions such as fever, headache, widespread fatigue, chills, arthralgia, muscular pain, and nausea [ 24 ] are transient and not discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
“…The concern for an association between SARS-CoV-2 vaccination and menstrual or bleeding disturbances in women has been triggered by the large number of spontaneous case reports related to such conditions. [1][2][3]10 Also, several studies on selfreported menstruation cycles changes after SARS-CoV-2 vaccination have been published. 4-9 27 28 The European Medicines Agency has recommended that heavy menstrual bleeding should be acknowledged as a side effect of both SARS-CoV-2 mRNA vaccines.…”
Section: Other Studies and Supportive Datamentioning
confidence: 99%
“…The US Vaccine Adverse Event Reporting System, the UK Medicines and Healthcare Products Regulatory Agency's Yellow Card surveillance scheme, and the Swedish Medical Products Agency have received many reports of menstrual disturbance after SARS-CoV-2 vaccination via their respective pharmacovigilance systems. [1][2][3] Several studies on self-reported menstruation cycles after SARS-CoV-2 vaccination, from survey data and a menstrual cycle tracking app, indicate changes in menstruation cycles. [4][5][6][7][8][9] A link between SARS-CoV-2 vaccination and menstrual disturbance has also doi: 10.1136/bmj-2023-074778 | BMJ 2023;381:e074778 | the bmj been widely discussed on social media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation